2019
DOI: 10.1103/physrevx.9.021018
|View full text |Cite
|
Sign up to set email alerts
|

Strain Localization Above the Yielding Point in Cyclically Deformed Glasses

Abstract: We study the yielding behaviour of a model glass under cyclic athermal quastistatic deformation computationally, and show that yielding is characterised by the discontinuous appearance of shear bands, whose width is about ten particle diameters at their initiation, in which the strain gets localised. Strain localisation is accompanied by a corresponding change in the energies, and a decrease in the density in the shear band. We show that the glass remains well annealed outside the shear band whereas the energi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
108
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(126 citation statements)
references
References 65 publications
14
108
1
Order By: Relevance
“…Further studies have argued that this oscillatory shear memory effect should apply to disordered systems in generalshearing causes rearrangement which continues until a reversible state is found [6][7][8]. Indeed, similar memory effects have been found in experiments and simulations of model amorphous systems [2,9,10], granular systems [11], and glasses [12][13][14][15]. The interactions between particles can vary and even the nature of the reversibility can vary for different systems [9,[16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 69%
“…Further studies have argued that this oscillatory shear memory effect should apply to disordered systems in generalshearing causes rearrangement which continues until a reversible state is found [6][7][8]. Indeed, similar memory effects have been found in experiments and simulations of model amorphous systems [2,9,10], granular systems [11], and glasses [12][13][14][15]. The interactions between particles can vary and even the nature of the reversibility can vary for different systems [9,[16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 69%
“…It should be emphasized that there is a crucial difference between rejuvenated states obtained via elastostatic loading and cyclic shear with the strain amplitude above the yield-7 ing point. In the latter case, the increase in the potential energy is directly related to the formation of a fluidized shear band [20,21,23,25], while in the former case, the plastic deformation under static stress is distributed more homogeneously in the regions with relatively low local yield stress. The next comment is regarding the structural characteristics at different energy states.…”
Section: Resultsmentioning
confidence: 99%
“…A number of recent molecular dynamics simulations studies have shown that disordered solids under cyclic loading either continue exploring deeper energy states at sufficiently small strain amplitudes or eventually undergo a transition to plastic flow within a shear band if the strain amplitude is above a certain value [18,19,24,25,28,29,33,34]. The precise determination of the critical strain amplitude, however, is a challenging problem because the number of cycles required to reach a dynamic steady state appears to diverge upon approaching the critical value [18,19].…”
Section: Resultsmentioning
confidence: 99%
“…The precise determination of the critical strain amplitude, however, is a challenging problem because the number of cycles required to reach a dynamic steady state appears to diverge upon approaching the critical value [18,19]. In addition, the estimate of the critical amplitude for binary glasses was shown to be system size [18] and temperature [17,29,33] dependent.…”
Section: Resultsmentioning
confidence: 99%